ACCEPTABILITY AND FEASIBILITY OF USING DIETARY NITRATE AND FOLATE SUPPLEMENTATION FOR THE TREATMENT OF HYPERTENSION IN A RURAL TANZANIAN POPULATION. (April 2021) - Prabhakar, Meghna; Kandhari, Navneet; Mmbaga, Blandina; Rogathi, Jane; Gray, William; Paddick, Stella-Maria; Walker, Richard; Siervo, Mario
Abstract : Objective: There is a substantial and growing burden of hypertension and hypertensive related disease in Tanzania. Low-cost and effective interventions are urgently needed. Little evidence is available on the use of inorganic nitrate and folate for treating hypertension in Africans. This study aims to assess the acceptability and feasibility of using nitrate supplementation in the form of beetroot juice and folate as a combined dietary intervention in a hypertensive Tanzanian population. Design and method: A three-arm, parallel, placebo controlled randomised clinical trial was conducted. Acceptability was assessed by one-to-one interviews, compliance and study retention rate. Trial assessments included clinic and ambulatory blood pressure measurements, electrocardiography, salivary samples, and blood samples. Results: Forty-eight participants were randomised for intervention. Forty-six participants completed the feasibility questionnaire. Twenty-six (57%) did not know what hypertension was and 37 (80%) had never heard of beetroot. Forty-two (91%) participants were happy to have the ambulatory blood pressure measurements repeated. All participants reported to have a >90% compliance to the dietary supplements. Conclusions: Awareness and knowledge of hypertension and the dietary interventions were low. Despite this, the interventions and protocol were well tolerated. This pilot shows that a dietary intervention of this nature is acceptable to this population, and that our study protocol can be feasibly used for a future trial in this setting.